Factors influencing the customers' selection towards diminishing partnership of home financing : an empirical study - Nur Harena Redzuan (Institute of Islamic Banking and Finance,International Islamic university Malaysia, 2014)
This research paper sought to assess the elements of Islamic home financing and why customers choose the products. The main problem of this study is to investigate the selection criteria that influence customers in adopting the diminishing partnership of Islamic financing transaction in purchasing a house. It is to determine the key factors among selection criteria of home financing, where the factors of ranking will be provided. This study is basically a survey method of quantitative approaches. A structured questionnaire was developed, pre-tested and personally administrated to the target population of existing home financing customers as well as potential home financing customers. One hundred and forty three (143) respondents were sampled from the target population using purposive sampling. This study focuses on innate characteristics and acceptance ofDP home financing, the respondents for this sampling were selected based on their knowledge in Islamic banking and finance field as to eliminate effects from imbalance marketing and promotionThe factors influencing selection of diminishing partnership are identified; "concept of equity financing", "method of computing and pricing of equity based", "Shariah compliance", "justice and equality", "societal wellbeing of society and equitable distribution" and "overall view and preference".Respondents rated the importance of these aspects along a Likert-type scale. The fivepoint scale was represented by the following anchors: 1 = Strongly Disagree, 2 = Disagree, 3 = Somewhat Agree, 4 =Agree, 5 = Strongly Agree. The study is conducted by using Exploratory Factor Analysis (EF A). The finding shows that the factor "Shariah compliance" was the first ranking as the reason for selection of DP home financing product preferred choice.On the external validity of findings, this study recommends for future research to expand the survey in a larger sample for a better accuracy. The EFA method can be enhanced by using confirmatory factor analysis. It would provide the pattern of correlation among the set of variables and confirm each item that constructs the variables.